2016
DOI: 10.1104/pp.16.00967
|View full text |Cite
|
Sign up to set email alerts
|

Secretory COPII Protein SEC31B Is Required for Pollen Wall Development

Abstract: The pollen wall protects pollen grains from abiotic and biotic stresses. During pollen wall development, tapetal cells play a vital role by secreting proteins, signals, and pollen wall material to ensure microspore development. But the regulatory mechanism underlying the secretory pathway of the tapetum is largely unknown. Here, we characterize the essential role of the Arabidopsis (Arabidopsis thaliana) COPII protein SECRETORY31B (SEC31B) in pollen wall development and the secretory activity of tapetal cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 95 publications
1
44
1
Order By: Relevance
“…Despite the low pollen germination rate, the atsec23a mutant was normally fertile, which may be due to the sufficient amount of functional pollen grains required for fertilization. Mutations in AtSEC24A , AtSEC24B , and AtSEC31B , other members of COPII, have also been shown to cause compromised pollen germination ( Conger et al , 2011 ; Tanaka et al , 2013 ; Zhao et al , 2016 ). During pollen germination, the growing pollen tube is encased only by the intine ( Chebli et al , 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the low pollen germination rate, the atsec23a mutant was normally fertile, which may be due to the sufficient amount of functional pollen grains required for fertilization. Mutations in AtSEC24A , AtSEC24B , and AtSEC31B , other members of COPII, have also been shown to cause compromised pollen germination ( Conger et al , 2011 ; Tanaka et al , 2013 ; Zhao et al , 2016 ). During pollen germination, the growing pollen tube is encased only by the intine ( Chebli et al , 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pollen wall integrity must be maintained to ensure normal pollen development. Mutations in genes that affect pollen wall integrity, such as MALE STERILITY1 ( MS1 ), MS2 , CALLOSE SYNTHASE5 ( CALS5 ), CYTOCHROME P450 ( CYP703A2 ), RUPTURED POLLEN GRAIN1 ( RPG1 ), DEFECTIVE IN EXINE PATTERNING1 ( DEX1 ), NO EXINE FORMATION1 ( NEF1 ), TRANSIENT DEFECTIVE EXINE ( TDE1 ), ATP-binding cassette transporter G26 ( ABCG26 ), and the COPII component AtSEC31B , have resulted in collapsed pollen grains with degenerated cytoplasm ( Aarts et al , 1997 ; Paxson-Sowders et al , 1997 ; Wilson et al , 2001 ; Ariizumi et al , 2004 , 2008 ; Dong et al , 2005 ; Morant et al , 2007 ; Guan et al , 2008 ; Choi et al , 2011 ; Paxson-Sowders et al , 2001 ; Zhao et al , 2016 ). Interestingly, the mutants dex1 , nef1 , tde1 , abcg26 , and atsec31b have accumulated sporopollenin-like aggregations on the middle layer similar to the atsec23ad mutant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MS26 encodes a cytochrome P450 monooxygenase and was found to function in the fatty acid metabolism pathway. Similarly, many tapetum‐expressed genes which are involved in fatty acid metabolism and lipid transporters are well known in rice, including WAX‐DEFICIENT ANTHER1 ( WDA1 ) (Jung et al ., ), DEFECTIVE POLLEN WALL ( DPW ) (Shi et al ., ), DPW2 (Xu et al ., ), CYP704B2 (Li et al ., ), POST‐MEIOTIC DEFICIENT ANTHER1 ( PDA1 ) (Hu et al ., ), CYP703A3 (Yang et al ., ), TAPETUM DEGENERATION RETARDATION ( TDR ) (Li et al ., ), DEFECTIVE TAPETUM CELL DEATH 1 ( DTC1 ) (Yi et al ., ), OsDEX1 (Yu et al ., ), OsC6 (Zhang et al ., ), OsABCG15 (Wu et al ., ), OsABCG26 (Zhao et al ., ), and MALE STERILITY2 ( MS2 ) (Chen et al ., ; Doan et al ., ), CYP704B1 (Dobritsa et al ., ), CYP703A2 (Morant et al ., ), Acyl‐CoA Synthetase ( ACOS5 ) (de Azevedo Souza et al ., ), and AtSEC31B (Zhao et al ., ) in Arabidopsis. The rice cyp703a3 mutant displays complete male sterility, whereas its Arabidopsis orthologous cyp703a2 mutant produces partially sterile pollen grains that display an abnormal exine with no obvious sporopollenin deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Main components of pollen exine are fatty acid derivatives and phenolics [ 27 , 28 , 29 ]. A growing number of genes have been identified that are important for pollen exine formation, such as MALE STERILITY2 [ 30 ], CYP703A2 and CYP704B2 [ 31 , 32 ]; RUPTURED POLLEN GRAIN1 ( RPG1 ), which are involved in fatty acid metabolism [ 33 ]; At5g62080 and At5g07230, genes encoding type III lipid transfer proteins [ 34 ]; AtbZIP34 , which encodes a bZIP-family transcription factor [ 35 ]; AtSEC31B , which encodes a secretory COPII protein [ 36 ]. Mutations of these genes usually cause severe pollen exine deposition or patterning defects, and lead to male sterility.…”
Section: Discussionmentioning
confidence: 99%